Optimizing Transaction Efficiency of Perumda Tirtauli Employees: The Role of Personal Financial Management and the Use of Mobile Banking with Financial Technology as a Mediator - Radiman Radiman; Sri Fitri Wahyuni; Nazwa Suzan (Lembaga Riset Ilmiah, 2026)
The rapid growth of digital financial services has increased the importance of understanding factors that influence transaction efficiency. However, limited studies have examined the mediating role of financial technology in the relationship between personal financial management, mobile banking usage, and transaction efficiency. This study aims to analyze the direct and indirect effects of personal financial management and mobile banking usage on transaction efficiency through financial technology among employees of Perumda Tirtauli, Pematangsiantar City. Using a quantitative associative approach, data were collected from all 100 permanent employees through a saturated sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and mediating relationships among variables. The results show that personal financial management and mobile banking usage do not directly affect transaction efficiency. However, both variables positively and significantly influence financial technology, which in turn has a significant positive effect on transaction efficiency. Financial technology mediates the effect of personal financial management on transaction efficiency but does not mediate the effect of mobile banking usage. This study highlights the important role of financial technology in enhancing transaction efficiency and contributes to the literature by explaining its mediating function in digital financial behavior.